2017
DOI: 10.13189/ujar.2017.050104
|View full text |Cite
|
Sign up to set email alerts
|

On-farm Conservation of Zaer Lentil Landrace in Context of Climate Change and Improved Varieties Competition

Abstract: Lentil (Lens culinaris Medik.) landrace of Zaer had been on-farm conserved thanks to ingenious farmers' practices. Farmers had selected, produced and maintained their landrace to satisfy their food security, ecological and economical needs. However, the increase of drought incidence had encouraged farmers to gradual abandonment of their landrace for L 56 improved variety to increase productivity and incomes. The landrace is therefore threatened for genetic drift by climatic change, varieties innovation and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Overall, this is more evident in Morocco compared to the northern Mediterranean countries included in this study, probably as a result of different farmer practices after drought episodes (more frequent in Morocco) that could have led to the reduction or loss of functional on farm seed reserve in a given region, thus introducing seeds of other landraces from different regions for the following cropping season. Benbrahim et al (2017) have observed similar fact in Zaer region of Morocco (northwestern). Same result was reported for Italian landraces by Viscosi et al (2010) who has obtained greater genetic variability within (56%) than among (44%) 12 landrace populations.…”
Section: Discussionsupporting
confidence: 69%
“…Overall, this is more evident in Morocco compared to the northern Mediterranean countries included in this study, probably as a result of different farmer practices after drought episodes (more frequent in Morocco) that could have led to the reduction or loss of functional on farm seed reserve in a given region, thus introducing seeds of other landraces from different regions for the following cropping season. Benbrahim et al (2017) have observed similar fact in Zaer region of Morocco (northwestern). Same result was reported for Italian landraces by Viscosi et al (2010) who has obtained greater genetic variability within (56%) than among (44%) 12 landrace populations.…”
Section: Discussionsupporting
confidence: 69%
“…On-farm conservation of crop genetic resources is a prerequisite for sustainable food production because this practice not only conserves the genetic resources of crops and evolutionary processes that involve diversity, but also the traditional knowledge system [ 30 ]. Many studies have focused on on-farm conservation for different crop varieties recently, including studies of vegetable landraces in the Korça region [ 31 ], a lentil landrace of Zaer [ 32 ], horticultural crops and wild fruit species in central Asia [ 33 ], and indigenous fruit species in Nigeria [ 34 ]. On-farm conservation can be enhanced by improving farmers’ perceptions [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…. Contrary, a low genetic differentiation revealed between Zaer promoted by a significant seeds geographical label linked to distinctive seed quality(Benbrahim et al, 2017). Thus, seeds exchange through farmer's involvement between uch as climate change resilience, consumers' sought phenotypic traits and organoleptic quality or by geographical proximity promotion as between FES-TET(1.17) , genetic differentiation among landraces could be attributed to both natural and human selection impact varied from 1.5 for both HCM and MBS to 7.6 for ZAER with an tent of gene differentiation (Phi'PT=0.664) relative to the total population variability) and relative to the maximum of attainable variability proportion (PhiPTmax=0,858) was independent to TET) to 0.880 (RHM-BM) was supported by ).…”
mentioning
confidence: 73%
“…Lentil is an important dietary source of proteins, fibers, macronutrients and micronutrients, vitamins, and antioxidant compounds (Han, (2005) In Morocco, lentil is produced mainly in low potential lands through the traditional farming system using landraces to insure home-consumption and livelihood security (Benbrahim et al, 2017). Seeds of lentil landraces constitute an economic dietary source of protein, essential minerals such as iron, zinc, calcium and magnesium, and antioxidant compounds (Benbrahim et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation